Oncolytic Viruses and Cancer, Do You Know the Main Mechanism? - Kooti, Wesam; Esmaeili Gouvarchin Ghaleh, Hadi; Farzanehpour, Mahdieh; Dorostkar, Ruhollah; Jalali Kondori, Bahman; Bolandian, Masoumeh (Frontiers in Oncology, 2021)
The global rate of cancer has increased in recent years and cancer is still a threat to human health. Recent developments in cancer treatment have yielded the understanding that viruses have a high potential in cancer treatment. Using oncolytic viruses (OVs) is the promising approaches in the treatment of malignant tumors. OVs can achieve their targeted treatment effects through selective cell death and induction of specific anti-tumor immunity. Targeting tumors and the mechanism for killing cancer cells are among the critical roles of OVs. Therefore, evaluation of OVs and understanding their precise mechanisms of action can be beneficial in the field of cancer therapy. The aim of this review study was to evaluated OVs and the mechanisms of their effects on cancer cells.